Cochlear Implant in Children:: The Parents’ Point of View - Yamanaka, Daniela Aparecida Rissi (2010)
The objective of this study was to analyze the point of view of parents in relation to the cochlear implant, their level of information concerning the implant, its risks and benefits, and their expectations towards their children´s future. Ten parents of deaf children candidate for the cochlear implant at Unicamp´s Clinical Hospital were interviewed. Based on a qualitative approach, a content analysis showed that the majority of parents seek the cure for deafness, and consequently, the acquisition of speech with the cochlear implant. For these families, the cochlear implant is seen both as the solution to their children´s deafness and as a path for a better future. It has been evidenced that during the acquisition of knowledge about the implant, parents experienced anxiety and anguish when faced with the risks and benefits of the procedure, and the need to choose between performing and not performing the cochlear implant.